The efficacy of electroacupuncture for cervical nerve edema and movement disorder caused by the brachial plexus injury: a case report - Wang, Chao; Liu, Yingjun; Li, Lu; Zhang, Haijuan; Ye, Ziyu; Zhao, Linfang (Frontiers in Neurology, 2024)
The brachial plexus injury (BPI) is one of the most severe types of peripheral nerve injuries, often caused by upper limb traction injury. In clinic, the surgery is widely used to treat the BPI. However, surgery may need to be performed multiple times at different stages, which carries risks and brings heavy economic burden. In non-surgical treatment, splinting, local injection of corticosteroids, and oral corticosteroids can achieve significant short-term benefits, but they are prone to recurrence and may cause complications of mechanical or chemical nerve damage. In this report, we present a case of a 46-year-old female patient with BPI. The patient had difficulty in raising, flexing and extending of the left upper limb, and accompanied with the soreness and pain of neck and shoulder. After three months of EA treatment, a significant reduction in the inner diameter of the left C5 to C7 root at the outlet of brachial plexus nerve was detected by musculoskeletal ultrasound, and the soreness and pain in the left neck and shoulder were significantly reduced. The soreness and 2 pain in the left neck and shoulder did not recur for two years.